Responding to Bullying Victimization: Comparative Analysis of Victimized Students in General and Special Education. (September 2017) - Hartley, Michael T.; Bauman, Sheri; Nixon, Charisse L.; Davis, Stan
Focused on 3, 305 students who self-reported frequent bullying victimization, this study compared the use and effectiveness of responses to address bullying victimization among students in special education, as compared with students in general education. Students in special education were less likely to make a joke, but more likely to tell the aggressor how they felt, hit the aggressor, and tell an adult at school and home, according to self-report. Furthermore, students in special education were significantly more likely to report that "things got worse" after using each response. Implications for educational policy and future research are discussed. Correction notice for 'Responding to Bullying Victimization: Comparative Analysis of Victimized Students in General and Special Education' by Michael T. Hartley, Sheri Bauman, Charisse L. Nixon, and Stan Davis, published in the Journal of Disability Policy Studies, 2017, Vol. 28(2) 77–89, DOI 10.1177/1044207317710700 This article reviews data from the Youth Voice Project national study of U.S. students in Grades 5 through 12 (Davis & Nixon, youthviolenceproject.com). The authors also referred to data from the Youth Voice Project in their article titled 'Comparative Study of Bullying Victimization Among Students in General and Special Education' by Hartley, Bauman, Nixon, and Davis, published in Exceptional Children, 2015, Vol. 81(2) 176–193, DOI: 10.1177/0014402914551741 (the "2015 Article"), which examined victimization of special education students and general education students by bullies. Accordingly, this article includes similar themes, scholarship, and methods as their 2015 Article. Several sections of the Article reproduce unattributed excerpts that were originally published in the 2015 Article, including portions of Table 1 and text in the sections with headings Introduction, Method, Results, and Limitations, particularly as the sections pertain to the demographic data reported and analyzed. Notwithstanding these similarities, the data analysis in this article differs from the analysis in the 2015 Article. Whereas the 2015 Article examines victimization variables, this article reports specific data about how students address bullying victimization.